Scoping Review: Determinants of Stunting in Children Under Five - Astaria Br Ginting; Ridesman Ridesman; Ribur Sinaga; Rolasnih Lista Simbolon; Mesrida Simarmata; Luwes Rizky Andriani; Lilis Suryani Simatupang (Griya Eka Sejahtera, 2026)
Background: Stunting in children under-five years old is a chronic nutritional problem caused by inadequate nutritional intake, maternal health, poor sanitation, and low socioeconomic conditions that have long-term impacts on children's growth and development. This study aimed to identify predictive factors for the incidence of stunting among children under five years old in Indonesia, drawing on prior studies.Methods: This study used a scoping review approach. The PICO framework was used to search for articles and formulate research questions. The literature search was conducted using Google Scholar and the DOAJ. Data extraction for the seven eligible articles was conducted by seven individuals. Examining the article's abstract, research design, measurement techniques, data analysis, and title was the first step in the extraction phase. A tabular synthesis matrix was then constructed from the data summary to facilitate the analysis. Finally, we compared and contrasted each publication's methodology, study results, and empirical evidence from theoretical and conceptual perspectives. Of the seven articles considered for inclusion, seven reviewers extracted data.Results: The results show that exclusive breastfeeding, drinking water quality, waste disposal, the availability of healthy toilet facilities, stunting, age, male gender, history of measles, family size, sanitation, father's occupation, provision of supplementary food, complementary feeding, maternal knowledge, and family support are significant determinants of the incidence of stunting.Conclusion: One of the dominant factors influencing stunting in toddlers is exclusive breastfeeding.